Peningkatan Dukungan Kesehatan Jiwa Psikososial Covid-19 Melalui Teknik Relaksasi Lima Jari - Desak Made Ari Dwi Jayanti; Ni Made Nopitawati; Ni Luh Putu Thrisnadewi; Ni Kadek Yuni Lestari; I Nyoman Sudarma (Poltekkes Kemenkes Surakarta, 2022)
Background: The COVID-19 pandemic has raised psychosocial problems such as anxiety. Anxiety is a physiological response that arises due to the stressor experienced. Efforts to overcome these psychosocial problems are to provide Covid 19 Psychosocial Mental Health Support (DKJPS Covid 19), one of which is in the form of five-finger relaxation. This community service aims to provide psychosocial mental health support by increasing the participant's ability to perform five-finger relaxation. Methods: The method provides online training (in the network). Partners in this activity are residents of Gang Gelatik Batuyang Batubulan. The stages of implementing activities include pre-activities, activities and evaluations. Results: The results of this activity show that the participants' psychosocial mental health conditions are in good condition, service participants can do five-finger relaxation and are enthusiastic about participating in activities to provide support for mental health and psychosocial Covid 19. Conclusion: Five-finger relaxation can be applied daily as psychosocial mental health support Covid 19.